Integrating Social-Emotional Learning into Hybrid Platforms: A Model for Student Digital Wellbeing and Engagement - Ayna Nuriyeva; Orazguly Mammedov; Serdar Zeynalov (Journal Emerging Technologies in Education, 2024)
Background. The increasing demand for higher education to produce not only academically competent graduates but also socially responsible citizens has elevated the importance of integrating service learning into university curricula. Service learning combines academic instruction with community service, offering students opportunities to apply theoretical knowledge in real-world contexts while fostering civic engagement and personal development. Purpose. This study aims to explore how service learning experiences influence students’ civic responsibility, critical thinking, and practical skill acquisition. Method. Employing a mixed-method approach, data were collected from 142 university students through surveys, reflective journals, and focus group discussions over the course of a semester-long service learning project. Results. The findings demonstrate that students involved in structured service learning activities reported enhanced problem-solving skills, stronger communication abilities, and a deeper understanding of social issues. They also developed a heightened sense of empathy, civic duty, and teamwork. Conclusions. The research concludes that service learning serves as a transformative educational approach that bridges academic knowledge and societal relevance, promoting holistic student development. The implications suggest that institutions should institutionalize service learning as a core pedagogical strategy to meet the evolving needs of 21st-century education.